Teacher Education Graduates’ Performance as Predictor of Licensure Examination for Teachers Results - Esmeralda, Aileen; Perez-Espinosa, Janet (JPAIR Multidisciplinary Research, 2015)
High percentage of passers in the Licensure Examination for Teachers (LET) indicates the competence of the Teacher Education Program (TEP) graduates of State Colleges and Universities. Licensure tests are usually one of the several criteria necessary to qualify an entry into the teaching profession. This government examination is designed to identify professionals who have the desired level of competency to teach basic education. The study determined the extent of implementation of the TEP of Carlos Hilado Memorial State College (CHMSC) in relation to the academic achievement and performance of graduates in the LET. The descriptive correlational method specifically documentary analysis, with the mean, Pearson Product Moment (PPM) and ANOVA were used in this study. Findings revealed that the Teacher Education Program of CHMSC was well implemented. This concludes that the Bachelor in Elementary Education (BEED) group showed greater confidence in academics, indicating the need to enhance the level of academic preparation of the BSED group underscoring general education and major subjects during pre-service years. It further revealed that a significant relationship existed between the LET performance and the academic achievement of the BEED graduates. This means that the teacher graduates’ academic performance is a significant predictor in the LET.